Exploration on Practical Applications of Artificial Intelligence in the Field of Precision Oncology - Xinyu Meng (International Journal of Social Sciences and Public Administration, 2026)
Precision oncology is a new model for cancer treatment that will no longer use traditional all-or-nothing methods but rather tailor treatments to specific changes in genes and other factors that cause cancer in different people. As the number of dimensions in biomedical data has been rising, more powerful computing facilities are needed to process such a large amount of data. Systematically explore the applications of artificial intelligence in the field of precision oncology in this paper. Research has been conducted on the use of deep learning and machine learning algorithms for automatic detection and morphological classification of tumours and tissues in oncological medical images and digital pathology. Expand on the above and determine whether artificial intelligence can be employed to analyze large-scale multi-omics data and extract predictive genetic information. A prediction model will also be constructed to anticipate the actual impact and adverse effects on the public of new drugs and so on. Ultimately, this study has shown that artificial intelligence will be used to power high-precision oncology, and at the same time, some problems in infrastructure and future implementation plans need to be addressed.